CONTRIBUTIONS OF BETHEL FULL GOSPEL CHURCH (GBIS) HERMON BANGIL IN HISTORICAL AND SOCIO-RELIGIOUS CONTEXTS: Kontribusi Gereja Bethel Injil Sepenuh (GBIS) Hermon Bangil dalam Konteks Sejarah dan Sosial Keagamaan. - Gulo, Wiwi Kristiani Putri; Widodo, Priyanto; Wibowo, Satrio (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
As a place of worship, churches often not only play a role in the spiritual sphere but also play an important role in social life. This research aims to reveal the history of the formation of Bethel Injil Sepenuh Church (GBIS) Hermon in Bangil and analyze its role in the social life of the congregation. In terms of the data analysis process, this research is a study that adopts the historical method with a descriptive qualitative approach. In summary, since 1952, GBIS Hermon Bangil has represented the social, cultural and institutional journey of the church. In addition, it has been proven that the Church actively participates in the fields of education, health, economy, and inter-community relations. The diversity of the congregation supports the growth of intercultural cooperation, unity, and tolerance in the neighborhood. The researcher proposes comparative research on GBIS in other areas, documentation of church archives, and expansion of interfaith cooperation and educational institutions to strengthen the social function of GBIS Hermon Bangil.